High‐Throughput Growth of Wafer‐Scale Monolayer Transition Metal Dichalcogenide via Vertical Ostwald Ripening. Issue 42 (16th September 2020) - Seol, Minsu; Lee, Min‐Hyun; Kim, Haeryong; Shin, Keun Wook; Cho, Yeonchoo; Jeon, Insu; Jeong, Myoungho; Lee, Hyung‐Ik; Park, Jiwoong; Shin, Hyeon‐Jin
Abstract: For practical device applications, monolayer transition metal dichalcogenide (TMD) films must meet key industry needs for batch processing, including the high‐throughput, large‐scale production of high‐quality, spatially uniform materials, and reliable integration into devices. Here, high‐throughput growth, completed in 12 min, of 6‐inch wafer‐scale monolayer MoS2 and WS2 is reported, which is directly compatible with scalable batch processing and device integration. Specifically, a pulsed metal–organic chemical vapor deposition process is developed, where periodic interruption of the precursor supply drives vertical Ostwald ripening, which prevents secondary nucleation despite high precursor concentrations. The as‐grown TMD films show excellent spatial homogeneity and well‐stitched grain boundaries, enabling facile transfer to various target substrates without degradation. Using these films, batch fabrication of high‐performance field‐effect transistor (FET) arrays in wafer‐scale is demonstrated, and the FETs show remarkable uniformity. The high‐throughput production and wafer‐scale automatable transfer will facilitate the integration of TMDs into Si‐complementary metal‐oxide‐semiconductor platforms. Abstract : High‐throughput growth of monolayer transition metal dichalcogenides (TMDs) is developed on 6‐inch wafer scale. Periodically interrupting the precursor supply drives lateral growth via the surface diffusion of adatoms on the pre‐synthesized TMDs (vertical Ostwald ripening). The as‐grown TMD possesses high crystallinity with well‐stitched grains, and uniform electrical properties even after transfer by an etching‐free de‐bonding and bonding process.